Fabrication of lnxGa1-xN/GaN Multi-Quantum Well Structure for Green Light Emitting Diode on Patterned Sapphire Substrate by Metal Organic Chemical Vapour Deposition - Rais, Shamsul Amir Abdul; Najiha, Hayatun; Hassan, Zainuriah; Shuhaimi, Ahmad
In an effort to successfully fabricate lnGaN-based for green emitting devices on patterned sapphire substrate, the indium composition in lnxGa1-xN/GaN multi-quantum well structure is crucial because lower indium composition will shift the wavelength towards ultraviolet region. In this study, 4 micrometre of undoped GaN epilayer was deposited as a buffer layer prior to the growth structure. In order to complete the device, 6 pairs of lnGaN/GaN multiquantum well structure was sandwiched with a 500 nm of p-GaN layer and 300 nm of nGaN layer by metal organic chemical vapour deposition (MOCVD). In this research, the indium to gallium composition ratio was 4:1. The crystal and optical properties of the samples were characterized using field effect scanning electron microscopy, high resolution x-ray diffraction spectroscopy, and photoluminescence spectroscopy.